Coercivity engineering in Sm(Fe0.8Co0.2)12B0.5 thin films by Si grain boundary diffusion. (1st April 2022) - Bolyachkin, A.; Sepehri-Amin, H.; Kambayashi, M.; Mori, Y.; Ohkubo, T.; Takahashi, Y.K.; Shima, T.; Hono, K.
Abstract: Achieving a large coercivity in the SmFe12 -based compounds with excellent intrinsic magnetic properties is the main challenge toward the development of new high-performance permanent magnets. In this study, we investigated the effect of microstructural factors on coercivity using Sm(Fe0.8 Co0.2 )12 B0.5 thin films as a model system. The films were composed of columnar Sm(Fe0.8 Co0.2 )12 grains with [001] out-of-plane texture separated by ∼5 nm-thick (Fe, B)-rich amorphous intergranular phase. To decrease the Fe content in the intergranular phase and improve the magnetic isolation of Sm(Fe0.8 Co0.2 )12 grains, grain boundary diffusion of Si was performed, which led to an increase in coercivity from 1.11 T to a record high value of 1.32 T for the Sm(Fe0.8 Co0.2 )12 compound. Detailed microstructure characterization using scanning transmission electron microscopy (STEM) and atom probe tomography (APT) confirmed that Si diffused in-part into the intergranular phase which became depleted of Fe and Co. Micromagnetic simulations on a model constructed based on STEM images have shown that triple junctions of the intergranular phase can act as nucleation centers during demagnetization process. This detrimental effect can be suppressed by full-depth diffusion of Si weakening the ferromagnetism of the intergranular phase. However, the presence of α-(Fe, Co) grains at the interface with a V underlayer substantially reduces the benefits of grain boundary diffusion. Thus, high coercivity in the SmFe12 -type magnets cannot be obtained unless the soft magnetic α-(Fe, Co) phases are eliminated. Graphical abstract: Image, graphical abstract .